2007
DOI: 10.1007/s00520-007-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Music imagery for adults with acute leukemia in protective environments: a feasibility study

Abstract: Music imagery is feasible for adults with acute leukemia in protected environments. Patients with lower initial distress may benefit from a music imagery program in terms of reduced anxiety at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 27 publications
0
44
1
3
Order By: Relevance
“…19,22,23,26,28 Two studies (15%), however, did not report these findings. 20,21 In fact, both of these studies reported contrary findings where the intervention group reported greater anxiety.…”
Section: Anxiety Findingscontrasting
confidence: 52%
See 1 more Smart Citation
“…19,22,23,26,28 Two studies (15%), however, did not report these findings. 20,21 In fact, both of these studies reported contrary findings where the intervention group reported greater anxiety.…”
Section: Anxiety Findingscontrasting
confidence: 52%
“…Patients were allowed to listen to music at anytime over the course of treatment with the exception of their radiation sessions In addition to variability in length of intervention sessions, there is also variability in number of intervention sessions. Eight studies tested interventions that were delivered on one occasion 19,21,22,[24][25][26]29,30 Burns et al 28 Three of the interventions delivered live music. 18,20,25 Burns et al 28 did not specify how the music was delivered and the remaining 9 studies delivered music through headphones or earphones.…”
Section: Nature Of Interventionsmentioning
confidence: 99%
“…Ferrer (92) compared live music to a no treatment control condition among cancer patients receiving chemotherapy and reported significantly less fatigue in the music group. Burns et al (93) compared music with standard care in a sample of hospitalized patients receiving intensive chemotherapy and found no significant difference in fatigue between groups.…”
Section: Resultsmentioning
confidence: 99%
“…The trials of music in reducing stress in cancer have not yielded consistent results; one study in women with metastatic breast cancer showed no significant differences in the music therapy led by a therapist and the usual care groups [173]. However, one study of music imagery intervention has suggested reduction of anxiety in adults undergoing chemotherapy, particularly those with lower initial stress levels [174]. …”
Section: Manipulative and Other Cam Therapiesmentioning
confidence: 99%